Influence of SO2 Molecule Deformation on the Manifestation of S–O Bond Deviation - Okhrimenko, B.A.; Yushko, O.O. (Ukrainian Journal of Physics, 2021)
The influence of a preliminary deformation of SO2 molecule by shifting either of the oxygen atoms from its equilibrium position on the manifestation of S–O bond deviation has been studied. The indicated deformation at a fixed position of the sulfur atom is shown to be accompanied by a variation in the equilibrium position of the other oxygen atom. The increase in the distance between the sulfur atom and either of oxygen ones gives rise to a reduction of the O–S–O angle.